Religion and Society According to Naima - COŞKUN, ALİ (KARABUK UNIV, 2015)
This article deals with the idea of religion and society according to Naima. In the first chapter, his ideas about the Ottoman Society of 17th century in terms of static and structural sociology of religion dealt with and in this frame the notions of organic society, class and religion were examined. This chapter especially focuses on religious scholars (ulama), traders, soldiers, civilian people (reaiyyah) and Kadizadeli movement. In the second chapter, the ideas of Naimaabout the Ottoman Society in terms of dynamic and functional sociology of religion dealt with and in this frame the theory of stages and sociology of great mandealt with. Finally, the social and religious reformation aspects of Naima were examined.
Keywords: Naima; Sociology of Religion; Organic Society; Religious Scholars; Ulama class; Traders class; Reaiyyah (civilian people); Kadizadeli Movement